PENGARUH BIAYA PRODUKSI DAN HARGA JUAL BAWANG MERAH TERHADAP PENDAPATAN PETANI PADA POKTAN SUMBER REJEKI DI DESA REJOSO KABUPATEN NGANJUK - Rima Novita Almatari; dewandaru, bothy; Afif Nur Rahmadi; M Dian Ruhamak (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research aims to determine the effect of production costs and selling prices on the income of shallot farmers. Nganjuk Regency was chosen as the research location because it is one of the national shallot stock areas. The influence you want to know is direct or indirect influence. This type of research is quantitative research which is an empirical research approach where the data is in the form of something that can be calculated/numbered. The respondents in this research were 91 POKTAN Sumber Rejeki farmers in Rejoso Village, Nganjuk Regency. Research data was obtained from questionnaires distributed to respondents. From the results of this test it can be concluded that production costs have a significant influence on farmer income. Meanwhile, the selling price has an insignificant influence on farmer income. The test results also show that production costs and selling prices have a simultaneous and joint influence on farmer income.